The natural history of neural tube defects in the setting of an Irish tertiary referral foetal medicine unit. (2nd January 2016) - Anglim, B.; Mandiwanza, T.; Miletin, J.; Turner, M.; Kennelly, M. M.
Abstract : Neural tube defects (NTDs) carry a heavy burden for affected individuals and their family. Physical and neurological outcome measures may help in counselling couples. The aim of this audit was to review all cases of NTDs seen at a tertiary referral foetal medicine unit. Cases were identified from obstetric, neonatal and neurosurgical records. Thirty-six cases of NTDs were identified. Of the 36, 25% ( n = 9, one trisomy 18) opted for termination of pregnancy abroad. Of the remaining 27, 19% ( n = 5) died in the antepartum period. 81% ( n = 22) were liveborn with four neonatal deaths (one trisomy 18). Of 15 cases, 14 had neurosurgical repair within a median time of 3 days and 9 of these also had a ventriculoperitoneal shunt inserted. Antenatal ultrasound accurately diagnosed lesion level in the majority of cases. The survival rate for babies diagnosed with non-lethal neural tubes defects is high when multidisciplinary care is initiated early.